Development of Computer Hardware Learning Media Using Augmented Reality: A Study on Student Engagement and Understanding - Ully, Rona; Nurdin, Enjang Ali; Rasim, Rasim (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop Augmented Reality-based learning media on computer hardware materials and investigate its impact on student understanding and engagement. The research employs the Research and Development (R&D) method with the ADDIE model. The study involved two lecturers as media experts, one informatics teacher as a material expert, and students in grades VIII-3 (control class) and VIII-4 (experimental class). Data collection techniques included interviews and questionnaires. Data analysis was conducted descriptively to assess expert validation and student involvement, as well as quantitatively through normality, homogeneity, t-test, and N-Gain calculation. The validation results showed that the media was highly feasible, with average scores of 97.5 from media experts and 62 from material experts. The N-Gain test revealed a greater increase in understanding in the experimental class (0.71) compared to the control class (0.41). Additionally, the average engagement score of students in the experimental class increased from 3.31 to 4.35, categorized as high, while the control class increased from 3.33 to 4.03, also categorized as high. The findings indicate that Augmented Reality-based learning media is feasible and effective in enhancing students' understanding and engagement with computer hardware materials.